A proposed guidance program to reduce the anxiety level of mothers of the pupils who are going to pass the baccalaureate exam - Haimudah, Jumaa Awlad (Arab Journal for Sciences and Research Publishing, 2017)
The study aimed to reveal the effectiveness of a guidance programme to reduce the anxiety level of mothers of the pupils who are going to pass the baccalaureate exam at Sidi A’baz secondary school in the wilaya of Ghardaia,Algeria.To achieve the study objectives,it was selected a sample of 35 mothers that had the highest grades on the scale of anxiety.The study was conducted on a sample of six mothers who accepted to attend the sessions of the guidance programme.The researcher used two tools:The Tyler’s anxiety scale whose psychometric properties were remeasured and a guidance programme to reduce the level of anxiety,prepared by the researcher, consisted of seven sessions for four weeks;the duration of the session ranged from 50 to 90 minutes.In order to answer the study questions,it was used the Mann Whitney Test.After the statistical analysis,the study results showed statistically significant differences between the mean scores of the mothers’ group in the pre test and the post test on the anxiety scale in favour of the post test.